RELIEF NARRATIVE ARJUNAWIWAHA DI GUA SELAMANGLENG DALAMPERSPEKTIF EDUKATIF - Y. Murdiyati, Y. Murdiyati (Jurnal Cakrawala Pendidikan, 2016)
Relief is onenf the decorations which was carved on the wall of temple.The most of the relieves of East Java style have rather flat form as wayang, different from the relieves of Centre Java style which have realistic form. There was the relief narrative Atjunawiwaha which was carved on the wall of Selamangleng Cave, which have an education values which was necessary to the continue generation to face the epoch challange globalisation. This matter to remember the education values of Indonesian more pale. Although properly the .,ducation values which was still relevance with the epoch development 2006/2007 percisted were defended, and the culture which not relevance with the need of Indonesian society could be left. In the asceticism scene contains belief in One God element, because the reached of purpose asceticism of was determined by the One God. It was location of the education value which was necessary planted to the children early. In the Goddess scene was expressed freely and naturally. The describe of female person who tempts a male person, conform with the character of East Javanese include the female person, who has the extrovert character. It’s different from the Centre Javanese who has the introvert character. There was also the ethic and aesthetic value, that was described in the Goddess scene with low level, it means they honor Atjuna. In the Bethara Guru scene gave a Pasopati heirloom to Arjuna to killed Newatakawaca, indicated that Arjuna was responsible to reach the purpose. The scene of Arjuna and Dewi Supraba went together to k.iIIed Newatakawaca, indecated there were an union and unit value between the Arjuna and Supraba. Thus in the relief of Selamangleng Cave contains a lot of educational values which was necessary transmited to the continue generation